THE IMPLEMENTATION OF ROLE-PLAYBASED ACTIVITIES: WHAT EFL STUDENTS LEARNED - Mardiningrum, Arifah (Journal of Foreign Language Teaching and Learning, 2016)
Role-play pedagogy has been implemented in higher education in various fields with varied procedures. Its ability to foster language learning and certain soft-skills has been investigated in myriad of studies. The current study investigated five EFL students? experiences and their perception of those experiences to seek for deeper understanding of their learning. The study took place in an English Department in a university in Yogyakarta, Indonesia. The data for this qualitative research were taken by in-depth interviews through online video calls. The finding is categorized into four themes. The first theme, rehearsal aspect, talks about the students? experience that seems to have a connection to their perception of the simulated play and a real-life situation. The second theme is related to students? preparedness and their action of assessing themselves. The third finding talks about students? experience in improvising in the role-play and how it makes them feel. Lastly, decision making becomes one of the theme emerging in the data. Two conclusions can be drawn from these finding, namely, that role-play can be a place for self-recognition, and that its preparation can be the key to shape the students? experience and perception.